An extended analytic model for the elastic properties of platelet-staggered composites and its application to 3D printed structures. (1st April 2018) - Kim, Youngsoo; Kim, Yongtae; Lee, Tae-Ik; Kim, Taek-Soo; Ryu, Seunghwa
Abstract: The load transfer mechanism in the unique staggered platelet structure of nacre has been intensively analyzed, and its structural features have been mimicked by various manufacturing methods such as 3D printing. However, due to the limited applicability of most analytical models and the limitations of 3D printers, it remains difficult to quantitatively predict and design the properties of nacre-inspired synthetic structures. In this study, we improve the analytic models to predict the effective elastic properties of various staggered platelet structures for a wide range of constituent materials' elastic moduli and geometric parameters by carefully accounting for the volume average of elastic properties. We also systematically investigate the effect of the printing orientation and width of the composite structure fabricated by a 3D printer. We show that our improved analytic model accurately predicts the properties of a 3D printed composite when the manufacturing-condition-dependent material properties are used as input. Our study reveals the origin of discrepancy between theory and 3D printed structures and enables a rational design of nacre-inspired structures.